A mobilidade da cidade aos pedaços: espaço-tempo-corpo dos deslocamentos em Belo Horizonte - Marcelo Cintra do Amaral (2015)
It is the transdisciplinary approach between mobility, urban and environmental, with the premise of the strong link between the economic processes, urban and mobility policies and spaces produced. Inspired by the work of Henri Lefebvre concerning urban, the thesis brings two complementary theoretical contributions, proposed to carry out the approach of the spatio-temporal processes of the city of Belo Horizonte: the use of the triad space-time-body for reading of urban processes relating to mobility, taking time as articulator dimension; andthe inseparability between city and mobility, their location and mobility mechanisms between copresença places (social interaction).Belo Horizonte is presented as a spatio-temporal palimpsest and observed from its 40 Territories Shared management, using census data and the source and target Research for the composition of maps, charts and graphs that make up an Almost Atlas, inserted as Appendix.In addition to being a methodological contribution in line with dialectic approach proposal and bring clues to understand processes, look the city apart seems to be a privileged microscale which allows a transescalar approach between the next (these pieces) and the remote (the city and the Metropolis). In the end, it is noted that since the modernist urbanism to the proposed ecological neighborhoods in Europe, there's always been a search attempt to improve the city from"perfect pieces" and confirmed the importance of the time as a dimension of understanding, resulting from processes and even as possible public policy.